2006
DOI: 10.1021/jo061308x
|View full text |Cite
|
Sign up to set email alerts
|

Aminolysis of Y-Substituted Phenyl Diphenylphosphinates and Benzoates:  Effect of Modification of Electrophilic Center from CO to PO

Abstract: The effect of modification of the electrophilic center from C=O to P=O on reactivity and reaction mechanism has been investigated for aminolysis of Y-substituted phenyl diphenylphosphinates (1a-j) and benzoates (2a-i). The phosphinates 1a-j are less reactive than the benzoates 2a-i. The reactions of 2,4-dinitrophenyl diphenylphosphinate (1a) with alicyclic secondary amines resulted in a linear Brønsted-type plot with a beta(nuc) value of 0.38, while the corresponding reactions of 2,4-dinitrophenyl benzoate (2a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 36 publications
4
52
2
Order By: Relevance
“…The value of the Brønsted slope obtained in the SA aminolysis of 1 (β = 0.39 ± 0.02, R 2 = 0.99) is in agreement with those found in the concerted reactions of 4-nitrophenyl diphenylphosphinate with SA amines in DMSO-H 2 O 20:80 mol% (β = 0.38) [15,16] and the concerted pyridinolyses of methyl S-aryl thiophosphate and methyl aryl phosphate diesters in the same solvent mixture, β = 0.42 and 0.56, respectively [17].…”
Section: Sa Aminolysis Reactionsupporting
confidence: 86%
“…The value of the Brønsted slope obtained in the SA aminolysis of 1 (β = 0.39 ± 0.02, R 2 = 0.99) is in agreement with those found in the concerted reactions of 4-nitrophenyl diphenylphosphinate with SA amines in DMSO-H 2 O 20:80 mol% (β = 0.38) [15,16] and the concerted pyridinolyses of methyl S-aryl thiophosphate and methyl aryl phosphate diesters in the same solvent mixture, β = 0.42 and 0.56, respectively [17].…”
Section: Sa Aminolysis Reactionsupporting
confidence: 86%
“…Nucleophilic substitution reactions of esters with amines have intensively been investigated due to their importance in biological processes as well as in synthetic applications . Aminolysis of esters has been reported to proceed through a concerted mechanism or via a stepwise pathway depending on reaction conditions ( e.g ., nature of the electrophilic center, amines, and reaction medium) . Reactions of 2,4‐dinitrophenyl diphenylphosphinate ( 1 ) with primary and secondary amines have been reported to proceed through a concerted mechanism on the basis of a linear Brønsted‐type plot with β nuc = −0.4 ± 0.1 .…”
Section: Introductionmentioning
confidence: 99%
“…Aminolysis of phosphates and phosphinates has been investigated by kinetic studies [11][12][13][14]. Cook et al investigated the aminolysis of aryl diphenylphosphinates and related compounds in acetonitrile.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al studied the pyridinolysis of phenyl-substituted phenyl chlorophosphates in acetonitrile and proposed a concerted mechanism [12]. Um et al performed kinetic studies on aminolysis of aryl diphenylphosphinates and concluded that the reactions proceeded through a concerted mechanism [13]. They also extended their study to aminolysis of aryl diphenylphosphinothioates to investigate the effect of modification of the electrophilic center from P@O to P@S on reactivity and reaction mechanisms [14].…”
Section: Introductionmentioning
confidence: 99%